Novel Polymorphism in a Promoter of MBL2 Gene Result in Lower MBL Expression in Chronic Infection Caused by HCV - Jamal Jalal, Paywast (Kurdistan Journal of Applied Research, 2020)
The Pathogen Recognition Receptors (PRRs) is an active protein in the immune system. The PRRs that secreted in the liver and we addressed were L-ficolin, MBL and H-ficolin. Previous studies revealed that both MBL and L-ficolin were hampered the HCV entry and infectivity. However, H-ficolin impact still needs to be addressed more so as determining their role during HCV infection. For these purposes, we aimed to determine the effect of different level in the serum of these proteins on the HCV infection and treatment outcome. Initially, we selected (25) HCV positive patients and (25) HCV negative control patients from the Trent Cohort and Regional Haemophiliac Study and to present the differences in serum concentrations of MBL, H- and L-ficolin. The level of these proteins was measured by ELISA method and compared with each other based on the detected SNPs by PCR and sequencing methods in the responsible genes. Our results showed that the polymorphism at position -221 in the MBL2 promoter significantly reduce the level of MBL protein more than the SNP at position -551. Interestingly, a new deletion of six nucleotides [AGGAAG] detected in the promoter at position -319 to -324 that succeeded by four other mutations at position -328, -336, -349 and -427 in most of the analyzed sequences. The 6bp deletion was statistically decreasing the concentration of MBL below 1µg.mL-1, precisely among non-responder patients. In conclusion, the existence of the new deletion in the promoter region of MBL2 gene and the additional newly detected polymorphisms, reduce the level of MBL protein and as a result impacts on the response to treatment among HCV-infected patients.